El senderismo en la ciudad de Loja y la utilización del tiempo libre, colegio La Dolorosa año 2014 - Correa Contento, Ramiro Andrés (2015)
Hiking is a recreational activity that allows direct contact with the environment to the execution of natural movements, research pose the problem of lack of knowledge for hiking as a physical and recreational activities for youth Tenth Year Basic General Education College Anda Fiscomisional Vicente Aguirre, La Dolorosa morning section of the city of Loja, during their free time in the period 2013 - 2014, aiming to assess hiking as a physical-recreational activity for youth During his free time, resorting to scientific review deepening topics hiking and leisure, exploratory methodology, scientific and purposeful character besides methods of analysis, synthesis, induction and deduction investigating the problem was applied, To fulfill the objectives the techniques of observation, interview and survey, mainly be used.The universe of this thesis consisted of 33 students, with an average age of 14.5 years was the tenth year of basic general education, parallel B of the Education Unit Anda Fiscomisional Vicente Aguirre, morning section "La Dolorosa". It was determined the following results that the majority of young people do not know what is hiking and are not adequately using their free time in physical activities, which lead to health problems at this stage of growth, adolescence is not well channeled , suggesting consider walking as part of the use of free time scheduled, regular and frequent basis.